Effect of Diabetes Self-Management Education on Quality of Life in Patients with Type 2 Diabetes Mellitus: A Quasi-Experimental Study - Najwatussikha Najwatussikha; Argi Virgona Bangun; M. Budi Santoso (Jurnal Ners, 2026)
Type 2 diabetes mellitus is a chronic disease that requires continuous self-management to prevent complications and maintain quality of life. Diabetes Self-Management Education (DSME) has been widely promoted as a structured educational intervention to improve patients’ self-care behaviors. To analyze the effect of a DSME program on quality of life among patients with type 2 diabetes mellitus. A quasi-experimental pretest–posttest control group study was conducted among patients with type 2 diabetes attending the outpatient clinic at RSUD Majalengka, Indonesia. A total of 106 participants were recruited using purposive sampling and divided into intervention (n=53) and control (n=53) groups. The intervention group received a structured DSME program consisting of four sessions covering diabetes knowledge, physical activity, nutrition management, and pharmacological therapy. Quality of life was measured using the Diabetes Quality of Life (DQOL) questionnaire before and after the intervention. Data were analyzed using statistical tests to compare within-group and between-group changes. Participants who received DSME showed greater improvement in Quality of life scores compared with the control group. The intervention supported better self-management behaviors, improved understanding of disease management, and increased patient engagement in their care. significantly improves quality of life among patients with type 2 diabetes mellitus and can be considered an effective educational strategy in outpatient care settings.